Preliminary study on zinc removal from aqueous solution by sago wastes - Wahi, Rafeah; Kanakaraju, Devagi; Yusuf, Noor Ashikin (IDOSI Publications, 2010)
In this study, sago wastes were investigated for its potential in removing Zn from aqueous solution. The equilibrium adsorption level has been studied under varying conditions of time, initial metal ion concentration, adsorbent dose, particle size and pH. The adsorption parameters were analyzed using Freundlich and Langmuir models. Kinetics of adsorption of Zn on adsorbents were determined and correlation relationship between kinetics of Zn adsorption and with pseudo first order and pseudo second order rate was determined. The physico-chemical properties such as determination of functional groups, moisture content and ash content were also investigated. The adsorption of Zn increased with increasing treatment time and the equilibrium of the adsorption was attained after 40 minutes The data showed that at initial concentration of 5 mg/l, the percentage of Zn removal based on the particle sizes of 300 µm, 500 µm and 1200 µm are 74 %, 47.6 % and 55.4 % respectively. The percentages of removal increase after the initial concentration of Zn reach 40 mg/l to 100 mg/l and the percentage of Zn removal based on the particle sizes of 300 µm, 500 µm and 1200 µm at 100 mg/l are 6.93%, 7.78% and 10.03% respectively. The study shows that the adsorption gives an optimum value at pH 9, best fitted on Langmuir isotherm model with maximum capacity of adsorption of 10.4 mg/l and obey the pseudo second-order rate equation of adsorption kinetic. However, at pH 7 which represents the normal pH range in wastewater treatment, maximum Zn adsorption is only 0.45 mg/g. It is recommended that further complimentary study should be conducted, for instance the sago wastes should be modified chemically in order to further enhance the removal of heavy metals from solution.